Dating Violence At Adolescent In The STIKES Hang Tuah Pekanbaru - Rina Yulviana; Yessi Harnani; Asnita Asnita (Institute Of Computer Science (IOCS), 2020)
Dating Violence (DV) is any form of violent acts which be done against a couple, either physically, sexually, emotionally / psychological in a dating relationship. DV can cause physical and psychological impact. This research intends to knowing relation between knowledge, attitude, peer group influence, sex and conflict in the family with DV. The research be done in the STIKes Hang Tuah Pekanbaru. Type of the research quantitative analytic with cross sectional design. The number of sample as much 92 people with technique proporsionate stratified random sampling. Data analysis univariate and bivariate with chi-square test. The result of this research shows that there is no relation between knowledge, attitude, peer group influence, sex and conflict in the family with dating violence by ? value> ? (0.05). So it can be concluded that good knowledge, reject attitude of DV, not get influence from peer group, male sex and not have conflict in the family not guarantee a person to spared from DV. Adolescent should can think rationally, be more alert in undergoing a dating relationship and be more open to tell the problem to parents.